GUADALCANAL STRATEGIES: LESSONS LEARNED FOR ENHANCING NATUNA’S SURVEILLANCE SYSTEM BY INDONESIAN COAST GUARD - Seno, Ario; Firdaus, Elsa Aliya Rizqoh (Jurnal Pertahanan dan Bela Negara, 2024)
The reconquest of Guadalcanal by U.S troops on 9th February 1943 marked a pivotal moment in reclaiming Pacific islands from Japanese occupation. The strategic conditions of Guadalcanal during the Pacific War era bear similarities to Natuna facing Chinese aggressiveness, particularly regarding the ’Nine Dash Line’ claims, which extend to Indonesian waters around Natuna. This research aims to derive lessons from the Japanese defeat at Guadalcanal to emphasize the critical importance of developing a robust surveillance system in Indonesia’s outermost regions, especially Natuna. Utilizing a combination of Case Study and Historical Research methodologies, this study identifies strategic parallels between the U.S military actions in Guadalcanal and Chinese actions in the South China Sea. The findings underscore the necessity for the Indonesian Coast Guard (Bakamla RI) to enhance surveillance capabilities in Natuna to safeguard national sovereignty.